An Optimal L∞–error Estimate for an Approximation of a Parabolic Variational Inequality. (2nd January 2016) - Bencheikh Le Hocine, Mohamed Amine; Boulaaras, Salah; Haiour, Mohamed
ABSTRACT: In this article, an optimal error estimate for parabolic variational inequalities is studied. Existence and uniqueness of the solution is provided by the introduction of a constructive algorithm. An optimally L ∞ -asymptotic behavior in uniform norm is proved using the semi-implicit time scheme combined with the finite element spatial approximation. The approach is based on the concept of subsolutions.